Concept Philosophy Education of the Enlighteners of Turkestan - Namazova Yulduz Muzaffarovna (Zien Journals, 2022)
This article emphasizes the importance of developing the philosophy of education in raising the worldview, consciousness and thinking of a person. The article also analyzes the impact of innovations in the education system on the development of society through the ideas set forth in the works of the educator A. Fitrat.
Keywords: Educator; knowledge; politics; education